Factors contributing to obesity among healthcare workers in primary health care facilities in Lepelle-Nkumpi Sub-District, Limpopo Province - Mashita, Audrey Lehlogonolo (My University, 2023)
Background: Obesity is a significant public health issue worldwide, affecting various populations including healthcare workers. This research aims to look into the factors contributing to obesity among healthcare workers in primary health care facilities in the Lepelle-Nkumpi sub-district of Limpopo Province, South Africa. Method: Data were gathered from a sample of 174 healthcare workers using self-administered questionnaires as part of a quantitative and cross-sectional study design. The questionnaire included sections on sociodemographic characteristics, lifestyle factors, dietary habits, physical activity levels, and workplace-related factors. Based on their Body Mass Index, participants were categorized as underweight, normal weight, overweight, or obese. The data were analyzed with the Statistical Package for Social Science version 28 and descriptive statistics. Relationships were calculated at a 95% confidence level using the Chi-square test, and a p-value of 0.05 was deemed statistically significant. Results: The study found that 9.8% participants were severely obese, 38.5% were obese, and 27.6% were overweight. Several factors contribute to obesity amongst healthcare workers in the clinics of the Lepelle-Nkumpi sub-district. These factors include inadequate physical activity, poor habits and lifestyle behaviours, sedentary behaviour during leisure time, exposure to restaurants, unhealthy dietary habits, and workplace environmental factors or a demanding profession. Conclusion: These findings highlight the need for interventions targeting healthcare workers' obesity in clinics in the Lepelle-Nkumpi sub-district. Strategies such as workplace wellness programs, promoting physical activity during working hours, providing healthy food options in the workplace, and enhancing awareness and education on healthy lifestyle choices are recommended. A weight management program is also needed
Thesis (MPH.) -- University of Limpopo, 2024
Keywords: Obisity; Life-style factors; Body mass index; Primary health workers; Lepelle-Nkumpi subdistrict; Obesity -- Social aspects; Body mass index; Medical personnel; Health facilities